The Development and Instigation of the 3D Object Identification System - Meškauskas, R.; Jokužis, V. (Elektronika ir Elektrotechnika, 2006)
The experimental system for three-dimensional object identification was developed and investigated. A laser scanner and structured light scanner was designed and produced specially for this system. Advantages and weaknesses of every scanning method was explored and experimentally tested. The 3D object model reconstruction algorithm was developed for every scanning method and specialized programs were optimized for every application case. The principles of the 3D identification system are given and the algorithms used are listed in this work. Real projects developed on the basis of the 3D identification system and technical data of the equipment produced are also presented. Ill. 7, bibl. 5 (in English; summaries in English, Russian and Lithuanian).